PENGARUH DIMENSI PENAMPANG SALURAN DAN STABILITAS LERENG TERHADAP GERUSAN - Andri Kurniawan, S.T., M.T.; Hayu Rahayu, S.T., M.T. (LP3M, 2022)
The analysis from calculation of the planning Kalen Bawah Rubber Weir in Cilamaya has not been maximized, resulting in scouring and slope landslides. Therefore, restoring the function of the weir is necessary, considering that the weir is needed to overcome a problem that occurs. The method used to analyze the dimensions of the escape channel is using HEC-RAS, mean while the method used to analyze slope stability is using geoslope. Based on this analysis, it can be concluded that the water velocity that occurs increases significantly. The increase in velocity is caused by the narrowing of the channel cross section so that scouring occurs, both on the channel wall and the channel bottom. The evasion channel is not able to drain the discharge Q5 = 160.27 m3/s for the implementation of construction work within a period of 1 year. The avoidance channel experiences a 1 meter deep channel bottom erosion. This is caused by a significant change in water velocity, so that it can erode the escape channel The condition of the slope stability of the escape channel does not meet the specified safety standards, which results in a Safety Factor (SF) of 1.18 < 1.50